Sirtuin 1 Stimulation Attenuates Ischemic Liver Injury and Enhances Mitochondrial Recovery and Autophagy. Issue 8 (August 2016) - Khader, Adam; Yang, Weng-Lang; Godwin, Andrew; Prince, Jose M.; Nicastro, Jeffrey M.; Coppa, Gene F.; Wang, Ping
Abstract : Objectives: Hepatic ischemia-reperfusion is a major clinical problem with limited treatment options. The pathophysiology of hepatic ischemia-reperfusion is characterized by mitochondrial dysfunction and cellular energy deficits. Sirtuin 1 is an energy-sensing enzyme known to modulate mitochondrial biogenesis. We hypothesized that pharmacologic activation of sirtuin 1 is protective after hepatic ischemia-reperfusion injury. Design: Animal study. Setting: University-based experimental laboratory. Subjects: Wild-type C57BL/6 mice. Interventions: C57BL/6 mice were subjected to 60-minute partial hepatic ischemia-reperfusion and posttreated with sirtuin 1 activator, SRT1720 (20 mg/kg), or vehicle. Blood and liver were collected at 24 hours after ischemia-reperfusion for analyses of hepatic injury, adenosine triphosphate levels, mitochondrial mass, autophagy, inflammation, and oxidative stress. H4IIE hepatoma cells and rat primary hepatocytes were incubated with oxyrase to induce hypoxia followed by reoxygenation in the presence or absence of SRT1720 for assessment of mitochondrial mass, mitochondrial membrane potential, and autophagy. Measurements and Main Results: SRT1720 restored the reduction in mitochondrial mass, enhanced autophagy, and preserved adenosine triphosphate levels in the liver after ischemia-reperfusion, which was associated with a decrease in ischemia-reperfusion–induced hepatic injury, apoptosis, and necrosis. Ischemia-reperfusion–induced inflammation was also significantly reduced by SRT1720 as measured by systemic and hepatic cytokine and chemokine levels, as well as a decrease in neutrophil infiltration to the liver. Furthermore, oxidative stress was markedly attenuated in the SRT1720-treated mice compared with the vehicle. SRT1720 treatment increased adenosine triphosphate levels and survival of cultured hepatocytes after hypoxia-reoxygenation. SRT1720 not only increased the mitochondrial mass but also increased mitochondrial membrane potential per cell in cultured hepatocytes after hypoxia-reoxygenation. Moreover, SRT1720 prevented the hypoxia-reoxygenation–induced mitochondrial depolarization and resulted in an enhancement of autophagy in cultured hepatocytes after hypoxia-reoxygenation. Conclusions: Pharmacologic stimulation of sirtuin 1 attenuates liver injury after hepatic ischemia-reperfusion by restoring mitochondrial mass and membrane potential, which is associated with the enhancement of autophagy. Abstract : Supplemental Digital Content is available in the text.